Few-body hierarchy in non-relativistic functional renormalization group equations and a decoupling theorem - Flörchinger, Stefan (Nuclear physics. A, Nuclear and hadronic physics, 2014)
For non-relativistic quantum field theory in the few-body limit with instantaneous interactions it is shown within the functional renormalization group formalism that propagators are not renormalized and that the renormalization group equations of one-particle irreducible vertex functions are governed by a hierarchical structure. This hierarchy allows to solve the equations in the n-body sector without knowledge or assumptions about the m-body sectors where m>n.